Interstitial effects of B addition on the metamagnetic transition and magnetocaloric effect in tetragonal Cu2Sb-type Mn1.95Cu0.05Sb alloys. (November 2017) - Zhou, Xiaoqian; Zhong, Hui; Yu, Dedong; Cui, Weibin; Liu, Tie; Wang, Qiang
Abstract: Mn1.95 Cu0.05 SbBx (x = 0, 0.06 and 0.1) alloys had been prepared and B interstitial effects on metamagnetic transition were studied. The metamagnetic transition temperature was reduced and thermal hysteresis was widened by higher B concentration. The saturation magnetization and the magnetic entropy change were increased by moderate amount of B addition. However, too high B composition led into the sluggish metamagnetic transition. By relating with crystallographic structure, our results further indicated that the electron density of the atoms at MnⅡ position plays critical role on influencing the metamagnetic transition in tetragonal Cu2 Sb-type Mn1.95 Cu0.05 Sb alloys. Highlights: Reduced metamagnetic transition temperature by interstitial B atoms. Increased spin reorientation temperature by interstitial B atoms. Moderate interstitial B composition beneficial for enhanced magnetocaloric effect. Electron density at MnⅡ sites experimentally proved to be critical for metamagnetic phase transition.